2012
DOI: 10.3149/fth.1001.6
|View full text |Cite
|
Sign up to set email alerts
|

Elements of Promising Practices in Fatherhood Programs: Evidence-Based Research Findings on Interventions for Fathers

Abstract: Over the last two decades there has been an increased societal and academic interest in the role of fathers, as well as promoting responsible fatherhood in families and communities. In turn, this interest has given rise to an increasing number of fatherhood interventions. Although many programs to support fatherhood exist, they often differ in terms of their goals, target populations, designs, methods of implementation and assessment. This article reviews key evaluation findings from fatherhood programs that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 44 publications
0
41
0
1
Order By: Relevance
“…Heightened awareness of paternal influences on children's development, particularly in combination with limited research on fathers relative to mothers, has prompted researchers to recommend that fathers be included in child and parenting studies and that targeted efforts be made to include them in the provision of parenting services (McWayne et al, 2013). The number of fathering interventions has begun to increase; however, these interventions mostly target specific high-risk groups (e.g., divorced fathers, teen fathers, incarcerated fathers), and few have been rigorously evaluated (Bronte-Tinkew, Burkhauser, & Metz, 2012). Further, programs for fathers typically support fathers' parenting involvement and aim to increase their parenting confidence rather than teach specific parenting skills that affect child outcomes (Stewart-Brown, 2006).…”
Section: The Role Of Fathers In Parentingmentioning
confidence: 99%
See 1 more Smart Citation
“…Heightened awareness of paternal influences on children's development, particularly in combination with limited research on fathers relative to mothers, has prompted researchers to recommend that fathers be included in child and parenting studies and that targeted efforts be made to include them in the provision of parenting services (McWayne et al, 2013). The number of fathering interventions has begun to increase; however, these interventions mostly target specific high-risk groups (e.g., divorced fathers, teen fathers, incarcerated fathers), and few have been rigorously evaluated (Bronte-Tinkew, Burkhauser, & Metz, 2012). Further, programs for fathers typically support fathers' parenting involvement and aim to increase their parenting confidence rather than teach specific parenting skills that affect child outcomes (Stewart-Brown, 2006).…”
Section: The Role Of Fathers In Parentingmentioning
confidence: 99%
“…For example, these programs tend to be designed for and marketed to women rather than men, and they are often offered at times and in formats that appeal to women more than men (Fletcher, 2001). Father participation may improve if program designers consider the context of fathers' parenting and modify programs accordingly (Bronte-Tinkew et al, 2012;Lundahl et al, 2008). For example, programs should attempt to enhance fathers' sense of parenting efficacy, given that higher paternal self-efficacy positively affects father involvement as well as children's social-emotional outcomes (Baxter & Smart, 2011;Giallo, Treyvaud, Cooklin, & Wade, 2012;Kwok, Ling, Leung, & Li, 2013).…”
Section: The Role Of Fathers In Parentingmentioning
confidence: 99%
“…Magill-Evans et al's (2006) systematic review of the effectiveness of 12 interventions for fathers with infants or toddlers found that those interventions which involved active participation with children were associated with increased father-child interaction. More generally, research findings suggest that fathers prefer services that have been designed specifically for them, that provide the opportunity for them to spend time with their children and where they are able to access peer support (Ghate et al 2000;Lloyd et al 2003;Garbers et al 2006;Bronte-Tinkew et al 2007;Berlyn et al 2008;Bayley et al 2009). A recent mixed-method survey with 339 fathers and 1203 social workers involved in active child welfare cases in the USA revealed that fathers requested strengths-based, family-centred services (Huebner et al 2008).…”
Section: Making Services Relevant To Fathersmentioning
confidence: 99%
“…Apesar de já evidenciada a relevância do envolvimento paterno, ainda se nota a falta de intervenções direcionadas para o aprimoramento específico da atuação do pai junto a seu filho (Benzies, Magil-Evans, Hayden, & Ballantyne, 2013;Flippin & Crais, 2011), bem como a fragilidade metodológica desses programas, quando existentes (Bronte-Tinkew, Burkhauser, & Metz, 2012). Embora recentemente algumas intervenções para pais (homens) já tenham sido criadas, estas, no entanto, não contam com robustos procedimentos de avaliação do envolvimento paterno (Bronte-Tinkew et al, 2007;Lundahl, Tollefson, Risser, & Lovejoy, 2008;McAllister, Burgess, Kato, & Barker, 2012).…”
Section: Avaliação Do Envolvimento Paternounclassified